Optimasi Karakteristik Komponen Waterjet thruster terhadap Gaya Dorong Menggunakan Metode Taguchi - Seva, Marcell; Kurniawan, Zaldy; Hasdiansah, Hasdiansah (Jurnal Inovasi Teknologi Terapan, 2024)
Waterjet thruster is a technological breakthrough in ship propulsion system. The propulsion system has a very significant influence on ship operations. The waterjet thruster system consists of an inlet, waterjet pump, and turbo outlet. 3D Printing is one of the technological breakthroughs in the field of layer-by-layer manufacturing. 3D Printing is efficient in the world of manufacturing in making mechanical components, even prototypes. The combination of component characteristics will be arranged using Taguchi method with L9(33) orthogonal matrix. This study aims to optimize the combination of waterjet thruster component characteristics. It is concluded that the characteristics of waterjet thruster components have an influence on the thrust force produced. The highest thrust force is in the 9th experiment with a thrust force of 2,281 Newton using a combination of the number of inlet blades of 5 pieces, the second type impeller, and the number of turbo outlet blades totaling 3 pieces.